Da’wah and Contemporary Ethics in the Islamic Perspective - Hasanah, Jamiatul; Wazis, Kun; Yohandi, Yohandi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
Dakwah as an Islamic propagation activity faces significant challenges in the contemporary era, particularly regarding human rights, pluralism, and gender issues. This research analyzes dakwah adaptation to modern ethical dynamics and the relevance of Islamic principles in providing constructive solutions. Employing a qualitative-descriptive approach, this study combines textual analysis of the Qur'an and hadiths with contemporary literature review and in-depth interviews with five active da'i and two Islamic studies academics. The research focuses on identifying ethical challenges in dakwah and exploring Islamic principles as guidance. Findings demonstrate that dakwah integrating universal Islamic values—justice, compassion, and respect for fellow beings—can synergize with human rights and pluralism principles, creating an inclusive social environment. Gender equality implementation in dakwah, through recognition of women's roles and contributions, strengthens women's positions without contradicting Islamic teachings. The research's practical implications provide guidance for da'i to adopt more adaptive and contextual approaches, including inclusive language usage, constructive dialogue toward differences, and deep understanding of contemporary social issues. Thus, Islamic dakwah can maintain its relevance while contributing positively to building a just, harmonious, and civilized society.